Helminth Parasites of Two Freshwater Fishes (Oreochromis niloticus and Clarias gariepinus) in Jibia Earth Dam, Katsina State, Nigeria. (Global Journal of Science Frontier Research, 2018)
Investigation on helminth parasitic fauna of two freshwater fishes Oreochromis niloticus and Clarias gariepinus was carried out from August 2016 to January 2017. A total of 242 fish samples comprising of 117 Oreochromis niloticus and 125 Clarias gariepinus of different weights and length groups were collected from Jibia earth dam, Katisina state, Nigeria and subjected to parasitological examination. The overall prevalence of infection recorded in the two fish species was 38.43%. Clariasgariepinus recorded the highest prevalence of infection of 46.40%. Helminth parasites recovered were mainly the trematode: Neascussp, nematodes: Procamallanus laevionchus and Contracaecum sp, cestodes: Polyonchobothrium clarias, Bothriocephalus aegyptiacus and Proteocephalus glanduliger and acanthocephalan: Neoechinorhynchus rutili. Helminthic infections were recorded in the skin, stomach and intestine though majority of infection was found in the intestine.
Keywords: jibia; katsina; helminth parasites; oreochromis niloticus and clariasgariepinus